Modelo de inspección de calidad para los procesos constructivos involucrados en la construcción de rampas aéreas en el AIJS - Chacón-Arias, Wándal Alberto (Instituto Tecnológico de Costa Rica, 2016)
The quality control methods applied by the companies during the execution of the projects allow to maintain good standards in productivity and to create an appropriate balance between the economic, administrative, technical, legal and social aspects. This project is focused on verifying the application of quality control methodologies through the development of an inspection model for construction-related processes related to the building of airfield facilities. The essential objective for this project is to create tools for planning and controlling as well as to improve existing ones, based on the criteria of quality and in response to a global diagnosis obtained from process analysis. The methodology used for fulfilling the respective scope of the project is divided into two stages. The first stage consists of activities such as the study of documentation, recognition of the work area, the analysis work programs and monitoring of construction processes. The second is technical and bibliographical research for selecting techniques the most effective inspection as well as the identification of the main problems affecting quality of production with their corresponding solutions to carry out an integrated proposal that seeks to improve the existing QMS. The results section consists of flowcharts, Ishikawa diagrams, checking lists, manuals of good practice, risk scenarios and matrix solution for the present problems. The inspection models are necessary to ensure the quality of process. The tools and researches conducted allowed generating a model inspection ensures the product´s quality and controls the work advance in the construction of airfield facilities.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Análisis; Procesos; Gestión de calidad; Sistemas